THEORETICAL FOUNDATIONS OF THE STATE OF CERTIFICATION OF THE PRODUCTION OF PRODUCTS OF THE TEXTILE INDUSTRY: https://doi.org/10.5281/zenodo.14759479 - Ergashev , Abrorbek (Journal of Contemporary World Studies, 2025)
This scientific article will study the theoretical foundations of certification in the process of manufacturing products of the textile industry, its significance and application in practice. Certification is considered as a necessary process to confirm the quality of products and ensure safety and reliability to consumers. The article analyzes the basic principles of the certification system in the textile industry, the various stages of certification organizations and the process, as well as the importance of compliance with international standards. The economic efficiency of this process and its role in improving the competitiveness of the industry are also mentioned.